The Way of No-Way to Pursue Knowledge in Many Ways (Invited Paper) - Jayanta Choudhury (Journal of Systemics, Cybernetics and Informatics, 2014)

(untitled)
"The Tao that can be told is not the eternal Tao. The name that can be named is not the eternal name. The nameless is the beginning of heaven and earth. The named is the mother of ten thousand things. Ever desireless, one can see the mystery. Ever desiring, one can see the manifestations. These two spring from the same source but differ in name; this appears as darkness. Darkness within darkness. The gate to all mystery."–Lao Tsu (B.C. 2500) The above is an English translation of the first verse of the book "Tao Te Ching" by Lao Tsu. A working meaning of the word "Tao" is "way". The technical jargon "multidisciplinary research" or "interdisciplinary research" are research in many named established areas (i.e. chemistry, physics, sociology, mathematics, statistics, theology, philosophy, political science etc.) by an individual or a group of individuals. This type of research has a mysterious common theme that cannot be isolated but is present in the manifestations in various research disciplines. One example of a common theme can be the goal of a new technological innovation. In this article, the problems and solutions of such endeavors are identified by practical analogies of living and nonliving natural phenomena to the above quoted verse by Lao Tsu.